If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (2(-7) + 4) = 10 Multiply 2 * -7 (-14 + 4) = 10 Combine like terms: -14 + 4 = -10 (-10) = 10 -10 = 10 Solving -10 = 10 Couldn't find a variable to solve for. This equation is invalid, the left and right sides are not equal, therefore there is no solution.
| 1/6*18 | | 100x=2x+3-4(2x+3) | | 8b+8= | | 2(3f+1)+4=4*-1-4(5+5f) | | 5y+3X+23=90 | | 15+x=-20 | | 9(x-2)=3(3x-6) | | 7*11=8u | | 16.58-2.6n-0.09=15-17.5n | | y=10+0.99x | | 250=24(5)+0.8x | | 24=2-9 | | 2*(-7)+4=10 | | 2x-2=x+67 | | 5x-102=180 | | 9v+21=4(v-6) | | 2x-13+2x+13=6x+10 | | 3x/3=48/3 | | 2p^2-5p-4=2 | | 42x+75=260 | | 13*17=8x | | 2(3f-1)+4=4*-1-4(5-1f) | | 5.18+8.1u=8.4u+11.09 | | 8(w+4)=-3w+21 | | z^17+2z^15-512=0 | | y-0=9(x+3) | | 2x+5x+1=-13 | | 4500e^(-x/150) | | -9(x-6)=-76.5 | | 2(3f-1)+4=4x-1-4(5-1f) | | 6v+37=-5(v-3) | | m/4-8=6 |